"Ogniem i mieczem" Henryka Sienkiewicza jako prefiguracja "fantasy" słowiańskiej = "With Fire and Sword" ["Ogniem i mieczem"] by Henryk Sienkiewicz as a prefiguration of Slavic fantasy - Piechota, Dariusz (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
"With Fire and Sword" has many features of fantasy novels and it is a prefigured modern Slavic fantasy. Sienkiewicz, using Old Polish, epic and romantic styling, rejects all forms of modernity. The author creates a dualistic vision of the world presented with a clear division into good (Polish-Lithuanian Commonwealth [Rzeczpospolita]) and evil (Ukraine). The space is enriched with elements of folklore with numerous references to Slavic myths, stories and legends about vampires and ghosts.
Keywords: Sienkiewicz, Henryk (1846-1916) - twórczość; fantasy; przestrzeń; bohaterowie; space; protagonists